LANGUAGE VARIATIONS OF K-POP FANS ON THE @CARATSTALK AUTO-BASE ACCOUNT IN X: SOCIOLINGUISTIC STUDY - dini, Wardini; Asfar, Dedy Ari; Syahrani, Agus (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
Abstract The research entitled